2004
DOI: 10.1002/ecjc.20163
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive sequencing method of the learning objects for the e-learning environment

Abstract: SUMMARYIn this study, an e-learning system is developed to handle the e-learning environment based on the learning ecological model. In the learning ecological model, which represents the comprehensive e-learning environment, not only the contents of learning, but also the learning environment are managed and provided, based on the content, the goal, and the configuration of the learning. The major purpose of this study is to realize the function that can manage the diversified learning objects with various in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…The results of their experiment have shown that learning in suitable learning paths could improve students' learning results and saves learning time. This result is in line with previously published studies [7,17,18], which have indicated that learning path adaptivity has successfully guided learner to get satisfactory assessment results.…”
Section: A Conceptualizing Learning Pathsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of their experiment have shown that learning in suitable learning paths could improve students' learning results and saves learning time. This result is in line with previously published studies [7,17,18], which have indicated that learning path adaptivity has successfully guided learner to get satisfactory assessment results.…”
Section: A Conceptualizing Learning Pathsupporting
confidence: 92%
“…Therefore, several authors [15,17] propose multi-criteria/multi-objective optimization problem to solve learning path adaptation. The concern in multi-objective optimization problem is to satisfy multiple objectives simultaneously.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Learning Ecological Model focuses on learning content, objective, and style (Seki et al (2000(Seki et al ( , 2002, Okamoto et al (2001)). RAPSODY is based on this model.…”
Section: Basic Idea: Rapsodylms Systemsmentioning
confidence: 99%
“…To realize this, LMSs must handle information such as user identity, curriculum, learning contents, learning history, communication among learners, questions, and answers (Seki et al (2002), Okamoto et al (2001), Ymakita et al (1999), IMS/GLC (2005)). RAPSODY systems (Seki et al (2000(Seki et al ( , 2002, Okamoto et al (2001)) implemented these features. In RAPSODY, learners and teachers can utilize functions such as computer supported cooperative learning (CSCL), authoring, planning curriculum, evaluation, and reporting.…”
Section: Basic Idea: Rapsodylms Systemsmentioning
confidence: 99%